2020
DOI: 10.3390/membranes10090221
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic Processes: Market Overview, Membrane Phenomena, Recent Developments and Sustainable Strategies

Abstract: In the context of preserving and improving human health, electrodialytic processes are very promising perspectives. Indeed, they allow the treatment of water, preservation of food products, production of bioactive compounds, extraction of organic acids, and recovery of energy from natural and wastewaters without major environmental impact. Hence, the aim of the present review is to give a global portrait of the most recent developments in electrodialytic membrane phenomena and their uses in sustainable strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 316 publications
(608 reference statements)
1
80
0
Order By: Relevance
“…The third direction is the use of AEMs in the food and pharmaceutical industries for the demineralization of proteins [ 8 ], tartrate stabilization of wine [ 9 ], separation of valuable anions of citric, malic, lactic acids and other organic nutrients [ 10 , 11 ]. In this case, the anion-exchange membranes should have sufficiently large pores that do not cause steric hindrances for the transport of large, highly hydrated anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third direction is the use of AEMs in the food and pharmaceutical industries for the demineralization of proteins [ 8 ], tartrate stabilization of wine [ 9 ], separation of valuable anions of citric, malic, lactic acids and other organic nutrients [ 10 , 11 ]. In this case, the anion-exchange membranes should have sufficiently large pores that do not cause steric hindrances for the transport of large, highly hydrated anions.…”
Section: Introductionmentioning
confidence: 99%
“…They allow the separation of streams of the ions, the joint presence of which in the concentrate can cause precipitation. Solving this problem revived interest in electrodialysis as an effective method for concentrating reverse osmosis retentates [ 14 ], deactivating mine and waste water [ 11 , 15 ], producing high-quality drinking water, water for irrigated agriculture [ 16 ], recovery of phosphates from municipal wastewater, livestock liquid effluent and landfills for the production of cheap fertilizers [ 17 ] as part of combined baro-electromembrane technologies. AEMs, which are selective to singly charged anions (systems Cl - /SO 4 2− , for example) [ 18 , 19 ] and are capable of resisting fouling, are essential for this purpose [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these phenomena contribute to the shortening of membrane lifetime [ 1 ]. In addition, it has been reported that the cost for cleaning membranes and replacing them vary from 40% to 50% of the cost of the product [ 2 , 3 , 4 ], while the cost of membranes and spacers contributes to 25–30% of the total cost of a new electrodialysis unit fully automated [ 4 ]. Furthermore, cleaning in place procedures require the use of chemicals such as acid, bases, and sometimes surfactant or enzyme solutions that can lead to the swelling of the polymer matrix and further contribute to the adsorption of high molecular weight compounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of membrane technology now is reaching beyond the well-known conventional applications of water treatment [ 13 ] and gas separation [ 14 , 15 ] into new exciting areas of biopharmaceutical purification [ 16 ] and power generation [ 17 ]. With better membrane materials and process innovations, the boundary of membrane technology will continue to expand wider.…”
Section: Membrane-based Flue Gas Dehydration: Three Different Techmentioning
confidence: 99%